Nonuniqueness of the solution of the gellerstedt space problem for one class of many-dimensional hyperbolic-elliptic equations - Aldashev, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
It is shown that the solution of the Gellerstedt space problem is not unique for one class of multidimensional hyperbolic-elliptic equations.